Making the case for Community Interpreting in health care: from needs assessment to risk management - Abraham, Diana; Fiola, Marco A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In Canada, community interpreting is little recognized and valued by public institutions, including those in the healthcare sector. Although many healthcare practitioners recognize the crucial role played by interpreters in delivering healthcare services, some of them ascribe to the notion that the inability to communicate with English-speaking or French-speaking patients is the patient ’s problem, and that any linguistic miscommunication which may occur is the responsibility of the patient. This attitude contributes to the degree to which healthcare practitioners rely on interpreting provided by family members, including children, without consideration either for risks of errors and omission or for potential violations of confidentiality, which are likely to occur when askingfriends or relatives to provide interpreting services. This “wall of resistance” has been deemed responsiblefor much of the difficulty experienced in Canada by immigrant and minority language advocacy groups in trying to ensure community interpreting services for immigrants, refugees and those Canadians with limited proficiency in English and/or French. A recently completed research studyfunded by the Government of Canada suggests that a paradigm shift may be operating in the healthcare sector, and that instead of still seeing language barriers solely as a human rights issue, language barriers should be considered from a risk-management perspective as well. This paper will review some of the mainfindings of this study.